Quantification of Tissue Oxygen Saturation in the Vastus Lateralis Muscle of Chronic Stroke Survivors During a Graded Exercise Test. Issue 1 (7th January 2023) - Hyngstrom, Allison S.; Nguyen, Jennifer N.; Uhrich, Toni D.; Wright, Michael T.; Gutterman, David D.; Schmit, Brian D.; Durand, Matthew J.
Abstract : Purpose: This study examined tissue oxygen saturation (StO2 ) of the vastus lateralis (VL) muscles of chronic stroke survivors during a graded exercise test (GXT). We hypothesized that the reduction in StO2 will be blunted in the paretic versus nonparetic VL during a maximum effort GXT. Methods: Chronic stroke survivors performed a GXT, and StO2 of the VL in each leg was measured using near-infrared spectroscopy. Twenty-six stroke survivors performed a GXT. Results: At rest, there was no difference in StO2 between the paretic and nonparetic VL (65 ± 9% vs 68 ± 7%, respectively, P = .32). The maximum change in StO2 from rest during the GXT was greater in the nonparetic versus the paretic VL (−16 ± 14% vs −9 ± 10%, respectively, P < .001). The magnitude of the oxygen resaturation response was also greater in the nonparetic versus the paretic VL (29 ± 23% vs 18 ± 15%, respectively, P < .001). VO2 peak was associated with the magnitude of the VL StO2 change during (r 2 = 0.54, P < .0001) and after (r 2 = 0.56, P < .001) the GXT. Conclusion: During a GXT, there is a blunted oxygen desaturation response in the paretic versus the nonparetic VL of chronic stroke survivors. In the paretic VL, there was a positive correlation between the oxygen desaturation response during the GXT and VO2 peak.